2013
DOI: 10.1371/journal.pone.0057591
|View full text |Cite
|
Sign up to set email alerts
|

Human SCARB2 Transgenic Mice as an Infectious Animal Model for Enterovirus 71

Abstract: Enterovirus 71 (EV71) and coxsackievirus (CVA) are the most common causative factors for hand, foot, and mouth disease (HFMD) and neurological disorders in children. Lack of a reliable animal model is an issue in investigating EV71-induced disease manifestation in humans, and the current clinical therapies are symptomatic. We generated a novel EV71-infectious model with hSCARB2-transgenic mice expressing the discovered receptor human SCARB2 (hSCARB2). The challenge of hSCARB2-transgenic mice with clinical isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
138
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(143 citation statements)
references
References 52 publications
4
138
1
Order By: Relevance
“…Alternatively, immunodeficient mice (29,30) and transgenic mice with a human EV71 receptor (31,32) were found to be vulnerable to EV71 infection. The AG129 mouse is immunodeficient and without alpha/beta and gamma interferon (IFN) receptors; it can be infected by the non-mouse-adapted EV71 strain 41 (EV71-B4 in this paper, where B4 indicates the subgenogroup) (30).…”
mentioning
confidence: 99%
“…Alternatively, immunodeficient mice (29,30) and transgenic mice with a human EV71 receptor (31,32) were found to be vulnerable to EV71 infection. The AG129 mouse is immunodeficient and without alpha/beta and gamma interferon (IFN) receptors; it can be infected by the non-mouse-adapted EV71 strain 41 (EV71-B4 in this paper, where B4 indicates the subgenogroup) (30).…”
mentioning
confidence: 99%
“…Similarly, Nishimura et al (15) reported that human P-selectin glycoprotein ligand-1(PSGL-1) can also facilitate EV71 infection in vitro. Recently, it was reported that human SCARB2 (hSCARB2) transgenic (Tg) mice can serve as an animal model of EV71 infection (16,17). While these receptor Tg mice can suffer limb paralysis upon i.p.…”
mentioning
confidence: 99%
“…In addition, it will be necessary to establish a scientific basis for this potential therapeutic role of GBA1 by conducting experiments in mouse models, e.g. assessing the ability of Cerezyme to control EV71 infection in vivo, although the relevance of small animal models to the pathology of EV71 in humans is still controversial [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, researchers reported the discovery of two EV71 receptors, i.e. human scavenger receptor class B, member 2 (SCARB2), also known as lysosomal integral membrane protein 2 (LIMP-2) or CD36b like-2; and P-selectin glycoprotein ligand-1 (PSGL-1), also known as CD162 [9][10][11]. SCARB2 is expressed in most cell types, whereas PSGL-1 is limited to blood cells and endothelial cells, suggesting a distinct role for these two receptors in the pathogenesis of EV71 infection in vivo [12].…”
Section: Introductionmentioning
confidence: 99%